2020
DOI: 10.1002/chem.202002303
|View full text |Cite
|
Sign up to set email alerts
|

The Application of a Y‐Modified Lanthanum Zirconate Flexible Thin Film for a High‐Performance Flexible Supercapacitor

Abstract: With the rapid developmento fw earable electronics devices, there is increasing demandf or the development of new flexiblee nergy storaged evices with high security, and this has become ah ot research topic. Although flexible supercapacitors are considered to be high-performance energy-storage equipment because of their fast charging/ discharging ability,long cycle life, good reliability,wide operating temperature range, and so on, there are still many drawbacks that need to be overcome. Herein, the La 2 Zr 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
2
9
0
Order By: Relevance
“…In past decades, alkyl dialkylcarbamodithioates and their derivatives have been widely reported for their excellent biological and pharmacological activities. For example, numerous investigations have shown that alkyl dialkylcarbamodithioates exhibit several bioactivities, such as antiproliferative, antiglaucoma, antibacterial, antifungal, spermicidal, and anti‐breast cancer . Furthermore, in vitro antitumor activities against human myelogenous leukemia K562 cells have been described for alkyl dialkylcarbamodithioates .…”
Section: Methodsmentioning
confidence: 99%
“…In past decades, alkyl dialkylcarbamodithioates and their derivatives have been widely reported for their excellent biological and pharmacological activities. For example, numerous investigations have shown that alkyl dialkylcarbamodithioates exhibit several bioactivities, such as antiproliferative, antiglaucoma, antibacterial, antifungal, spermicidal, and anti‐breast cancer . Furthermore, in vitro antitumor activities against human myelogenous leukemia K562 cells have been described for alkyl dialkylcarbamodithioates .…”
Section: Methodsmentioning
confidence: 99%
“…[60] Likewise, Cao et al doped Y element into La 2 Zr 2 O 7 samples to obtain La 2 Y x Zr 2-x O 3 nanofibers containing an increased oxygen vacancy content. [238] The optimized La 2 Y x Zr 2-x O 3 delivered the areal capacitance of 605.3 mF cm À 2 . Equally important, B-site cation as redox active sites can be composed of multiple redox metal ions.…”
Section: Re/perovskite Oxidesmentioning
confidence: 99%
“…In general, doping heterogeneous cations in A or B‐site cations of perovskite can improve conductivity or create more charge storage active sites, which is beneficial to its electrochemical properties [238,248] . For substitution in A or B‐site, Zhang and co‐workers explored Sr‐doped lanthanum cobaltate perovskite (La x Sr 1‐ x CoO 3‐ δ ).…”
Section: Re Compounds and Nanocomposites For Scs Applicationmentioning
confidence: 99%
See 2 more Smart Citations